Evaluation of the PLAC8 Gene in Mexican Women With and Without Preeclampsia and Obesity - Barragán-Zúñiga, Laura Jazel; Marchat, Laurence A.; Carrasco-Wong, Ivo; Blanco-Castaneda, Ricardo; Salas-Pacheco, José M.; Simental-Mendia, Luis Ernesto; Correa-Ramírez, Miguel Mauricio; Sosa-Macías, Martha; Gutiérrez, Jaime; Galaviz-Hernandez, Carlos (Frontiers in Medicine, 2022)
Preeclampsia is a leading cause of maternal-fetal mortality worldwide, and obesity is an important risk factor. Genes associated with pathophysiological events common to preeclampsia and obesity remain to be studied, such as PLAC8; therefore, the aim of the present study was to evaluate this gene in the placentas of women affected with preeclampsia and healthy pregnant women. This case–controlled study included 71 healthy and 64 preeclampsia pregnancies. Gene expression was evaluated in primary human cytotrophoblasts from 6 normal and 6 preeclampsia pregnancies, and protein expression was verified in placentas from five healthy and six preeclampsia pregnancies. The whole coding and 5´ regions of the PLAC8 gene were sequenced from healthy (n=10) and preeclamptic (n=10) pregnancies. The presence of the observed nucleotide variations was analyzed by RT–PCR in the total population. Statistical analyses were performed accordingly. Obesity was associated with severe preeclampsia (OR 3.34; CI 95% 1.3-8.2, p<0.01). Significantly higher mRNA and protein expression was observed in preeclamptic vs. healthy placentas (p<0.05). After sequencing, a single nucleotide variation was identified in 10 cases and one control (p<0.01), which was then evaluated in the total population showing no association with preeclampsia. This preliminary study confirms the association of severe preeclampsia with obesity and suggests higher expression of PLAC8 mRNA and protein in placentas from preeclampsia. No differences in nucleotide variations between cases and controls of the whole population were observed. Further research is required to evaluate the implications of higher gene/protein expression in preeclampsia and the causes of such variation.